The Influence Of Business Capital, Labor, On Income With Length Of Business As A Moderation Variable - Nur Adila, Asviana Bela; Mustahidda, Rahmania (SEAN Institute, 2024)
Micro, Small and Medium Enterprises (MSMEs) in the field of handicrafts are able to form a creative economy that can improve the welfare and economy of the community. This research aims to examine the variables that influence the income of handicraft MSMEs in Pucang Village, Secang District. This research aims to determine and analyze the effect of business capital and labor on income with length of business as a moderating variable. The population in this research is the MSME craft center in Pucang village, Secang subdistrict, totaling 60 business actors. The samples taken in this research used observation, interview and questionnaire methods. Data were analyzed using Social Science Statistics (SPSS) version 25 by carrying out descriptive tests, classical assumption tests and tests Moderating Regression Analysis (MRA). This research develops the results of business capital, labor, and length of business as moderating variables on income so that it can provide broader results than previous research. The results of this study show that the influence of business capital and labor has a significant effect on income, while business capital and labor which are moderated by income also have a significant effect on income. Business capital has a significant influence on income with a significance value of 0.001 < 0.05. Labor on income also has a significant influence on income with a significance value of 0.002 <0.05. Furthermore, length of business is able to moderate business capital on income with a significance value of 0.006 <0.05. Apart from that, the length of business is also able to moderate employment on income with a significance value of 0.000 < 0.05. In conclusion MSMEs in Pucang Village focus on increasing business capital and workforce quality. Additionally, they should consider the strategic development of their business over time to maximize revenue, taking advantage of the moderating effects of business longevity.